KONSEP METODOLOGI KAJIAN ISLAM - Mi’raj; Muhammad Bayu Akbar P; Wafikul Aziz; Damanhuri (Universitas Islam Lamongan, 2024)
This study explains the basic concepts of methodology in Islamic studies, highlighting the urgency and scope of methodology in the context of Islamic studies, recognizing its vital role in providing a framework for comprehensive scientific research. The research method employed is library-based, involving the exploration of library materials or secondary data, including primary sources such as books, journals, and other relevant resources related to the object of study. The findings of the research indicate that the application of appropriate methodology not only enhances the understanding of Islam but also has the potential to enrich cross-disciplinary knowledge and influence contemporary thinking about religion, all within the framework of a well-functioning and comprehensive Islamic education process. The implications of this research underscore the importance of understanding and applying the proper methodology in the praxis of Islamic education to address global challenges and strengthen the contribution of Muslims in an increasingly complex world.